2021
DOI: 10.3390/genes12071085
|View full text |Cite
|
Sign up to set email alerts
|

Alternative RNA Splicing—The Trojan Horse of Cancer Cells in Chemotherapy

Abstract: Almost all transcribed human genes undergo alternative RNA splicing, which increases the diversity of the coding and non-coding cellular landscape. The resultant gene products might have distinctly different and, in some cases, even opposite functions. Therefore, the abnormal regulation of alternative splicing plays a crucial role in malignant transformation, development, and progression, a fact supported by the distinct splicing profiles identified in both healthy and tumor cells. Drug resistance, resulting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 227 publications
(268 reference statements)
0
11
0
Order By: Relevance
“…Alternative splicing involves the removal of introns from pre-messenger ribonucleic acid (pre-mRNA), with the remaining exons being connected to each other in different combinations to form mRNAs [ 32 , 33 ]. When dysregulated, the generation of variants that promote tumorigenesis may occur [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Moreover, some of the variants formed from the alternative splicing of full-length or total VEGF are linked to impaired angiogenesis and tumor progression [ 35 , 36 ].…”
Section: Alternative Splicing Of Vegf and Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative splicing involves the removal of introns from pre-messenger ribonucleic acid (pre-mRNA), with the remaining exons being connected to each other in different combinations to form mRNAs [ 32 , 33 ]. When dysregulated, the generation of variants that promote tumorigenesis may occur [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Moreover, some of the variants formed from the alternative splicing of full-length or total VEGF are linked to impaired angiogenesis and tumor progression [ 35 , 36 ].…”
Section: Alternative Splicing Of Vegf and Angiogenesismentioning
confidence: 99%
“…When dysregulated, the generation of variants that promote tumorigenesis may occur [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Moreover, some of the variants formed from the alternative splicing of full-length or total VEGF are linked to impaired angiogenesis and tumor progression [ 35 , 36 ]. The discovery of several VEGF isoforms with distinct functions has revealed that the physiology of VEGF is more complex than previously thought [ 37 ].…”
Section: Alternative Splicing Of Vegf and Angiogenesismentioning
confidence: 99%
“…Tumors resistant to this are known as castration resistant PCa (CRPC) and are treated with androgen receptor (AR) blockers, such as Enzalutamide (Enza). Alternative splicing of the androgen receptor has been observed in CRPC [ 101 ]. An analysis of splicing events in drug resistant prostate cancer revealed alternative splicing events in RNA binding proteins that are under control of the Myc signaling pathway.…”
Section: Mirna and Alternative Splicing-induced Drug Resistancementioning
confidence: 99%
“…Among the diseases where cohesin mutations have been found is acute myeloid leukemia (AML), where mutations in cohesin components occur at a frequency of up to 20% (10)(11)(12). AML is frequently associated with large changes in patterns of alternative splicing, where it has been estimated that more than 2000 transcripts undergo altered splicing, with distinct patterns associated with chemosensitivity or resistance (13). Splicing in mammalian systems is mediated by the spliceosome, a multi-megadalton complex that assembles on intronic 5′ and 3′ splice sites (14).…”
Section: Introductionmentioning
confidence: 99%